China's New Multilateral Institutions: A Framework and Research Agenda - Matthew D. Stephen (International Studies Review, 2021)
As China has risen to the status of a global power, it has taken the lead in fostering several new multilateral institutional initiatives. Some of these are formal intergovernmental organizations; others are informal clubs, forums, or platforms. Collectively, these acts of institutional creation suggest that China is no longer content to “join” the existing global order but is constructing its own multilateral infrastructure. What do such institutions mean for global governance? This article provides a framework for studying such multilateral institutions and sketches an emerging research agenda. First, it provides a systematic empirical overview of China's participation in the creation of multilateral institutions between 1990 and 2017. Second, it develops analytical categories for describing types of new institutions based on their relationships with incumbent institutions. Central to this typology is (1) whether new multilateral institutions' governance functions are additive or rivalrous to those of existing ones, and (2) whether they promote congruent or distinct social purposes. Based on these characteristics, new multilateral institutions may be complementary, divergent, substitutive, or competing. Third, it considers the implications of China's multilateral institution-building for global governance in the context of an international power shift. – – A medida que China ha ido adquiriendo la condición de potencia mundial, ha asumido el mando de promover varias iniciativas nuevas relacionadas con las instituciones multilaterales. Algunas de estas son organizaciones intergubernamentales formales, mientras que otras son clubes, foros o plataformas informales. En conjunto, estos actos de creación institucional sugieren que China ya no está interesada en «unirse» al orden mundial actual, sino que está construyendo su propia infraestructura multilateral. Qué implican dichas instituciones para la gobernabilidad mundial? Este artículo ofrece un marco para el estudio de dichas instituciones multilaterales y describe brevemente un programa de investigación emergente. En primer lugar, ofrece una visión general empírica y sistemática de la participación de China en la creación de instituciones multilaterales entre 1990 y 2017. En segundo lugar, desarrolla categorías analíticas para describir los tipos de nuevas instituciones en función de sus relaciones con las instituciones vigentes. Un aspecto clave de esta tipología es (1) si las funciones de gobernabilidad de las nuevas instituciones multilaterales se adhieren o se oponen a las de las existentes y (2) si promueven propósitos sociales congruentes o distintos. En función de estas características, las nuevas instituciones multilaterales pueden ser complementarias, divergentes, sustitutivas o competidoras. En tercer lugar, se analizan las consecuencias de la creación de instituciones multilaterales por parte de China para la gobernabilidad mundial en el contexto de un cambio de poder internacional.
Keywords: 300; China; global governance; multilateral institutions; gobernabilidad mundial; instituciones multilaterales; gouvernance mondiale; institutions multilatérales